Factores determinantes del incumplimiento del esquema de vacunación en menores de 2 años del Centro de Salud N°3 del cantón Loja - Montaño Quizhpe, Cinthya Alexandra (2024)
Currently, non-compliance with vaccination schedules continues to be a significant public health problem in our country. For this reason, the present work of curricular integration has been proposed with the objective of determining the causes that intervene in the non-compliance of the vaccination scheme in children under 2 years of age of the Health Center N° 3 of the Loja canton. In this context, the research design was descriptive, quantitative and cross-sectional, carried out on 30 guardians of children under 2 years old, to whom a 47-item questionnaire was applied, validated by experts, using Fleiss' Kappa statistical coefficient. Among the main results, it was found that 83.33% of the caregivers are women, predominantly between 27 and 30 years of age (43.33%), 40.00% of whom are in union with their partner, and their main occupation is in the public sector (26.67%); In the case of infants, males predominated (53.33%) with ages from 7 to 9 months (56.67%); with respect to the vaccines with the highest percentage of delay, it was found that 30.00% correspond to those applied at 6 months of age (1st dose of bOPV, 3rd dose of pentavalent and pneumococcus); In relation to the factors linked to the delay in the vaccination schedule, the pediatric factor predominated, since the caregivers argued that the child was sick and that was the reason for not vaccinating him/her 23.33%, followed by forgetting the vaccination date and the limitation due to work schedules, which also had a significant percentage (20.00%). It is concluded that noncompliance with the vaccination schedule is a multifactorial phenomenon involving many aspects ranging from sociodemographic, cultural, cognitive, institutional and pediatric components